Analisis Kualitas Pelayanan Klaim Terhadap Kepuasan Konsumen Pada PT Asuransi Bhakti Bhayangkara Cabang Palembang - Marita Pratisila; Nanda Revita; Aras Tulip; Vivin Afini (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2023)
The aims of this study were to determine the effects of claim service quality on customer satisfaction at PT Asuransi Bhakti Bhayangkara Palembang Branch. This research was associative quantitative. The data collection method used was the census. Respondents in this study were all employees of the PT Asuransi Bhakti Bhayangkara Palembang Branch of i.e. 98 customers. The data collection tool used in this study was a questionnaire. The data were analysed using SPSS. The conclusions that can be drawn from this study were Claim Service Quality had a positive and significant effect on Customer Satisfaction at PT Asuransi Bhakti Bhayangkara Palembang Branch.